On determining the zenith angle dependence of the Martian radiation environment at Gale Crater altitudes. Issue 24 (31st December 2015) - Wimmer‐Schweingruber, Robert F.; Köhler, Jan; Hassler, Donald M.; Guo, Jingnan; Appel, Jan‐Kristoffer; Zeitlin, Cary; Böhm, Eckart; Ehresmann, Bent; Lohf, Henning; Böttcher, Stephan I.; Burmeister, Sönke; Martin, Cesar; et al.
Abstract: We report the zenith angle dependence of the radiation environment at Gale Crater on Mars. This is the first determination of this dependence on another planet than Earth and is important for future human exploration of Mars and understanding radiation effects in the Martian regolith. Within the narrow range of tilt angles (0≤ θ 0 ≤15°) experienced by Curiosity on Mars, we find a dependence J ∝ cos γ ′ ( θ ) with γ ′ = 1 . 18 ± 0 . 07, which is not too different from an isotropic radiation field and quite different from that at sea level on Earth where γ ′ ≈ 2 . 0 . Key Points: Mars surface radiation is unique and quite different from Earth We present the first measurement of the zenith angle dependence This has broad implications for exploration and understanding Mars history